SOME CONSIDERATIONS ON THE CONCEPT OF LIFE CRYSTALLIZATION - V.A. Popov (Минералогия)
To finish the elaboration of the concept of life crystallization suggested by Academician N.P. Yushkin, it is important to specify some definitions. We propose new formulations of the following terms: crystallization, life, mineral, cell and others. The natural crystallization, which causes the formation of self-organized systems, is a condition of life existence in the Universe. The existence of crystallization event is similar to the existence of the events such as gravitation, magnetism, electricity. N.P. Yushkin appealed to the scientific community to pay attention to the mechanism of functioning biological systems. Study and modeling of such systems should attract mineralogical methods, in particular, ideas on growth and dissolution of minerals and their aggregates. He suggested that the 21st century will provide a synthesis of alive and mineral worlds in scientific concepts.